Chitosan nanoparticles (ChNPs): A versatile growth promoter in modern agricultural production. Issue 11 (November 2022) - Ingle, Pramod U.; Shende, Sudhir S.; Shingote, Prashant R.; Mishra, Suchitra S.; Sarda, Vaidehi; Wasule, Dhiraj L.; Rajput, Vishnu D.; Minkina, Tatiana; Rai, Mahendra; Sushkova, Svetlana; Mandzhieva, Saglara; Gade, Aniket
Abstract: Agriculture is a backbone of global economy and most of the population relies on this sector for their livelihood. Chitosan as a biodegradable material thus can be explored for in various fields in its nano form to replace non-biodegradable and toxic compounds. The chitosan has appealing properties like biocompatibility, non-toxicity, biodegradability, and low allergenic, making it useful in several applications including in agriculture sector. Because of their unique properties, chitosan nanoparticles (ChNPs) are extensively applied as a bioagent in various biological and biomedical processes, including wastewater treatment, plant growth promoter, fungicidal agent, wound healing, and scaffold for tissue engineering. Furthermore, the biocompatibility of chitosan nanoparticles (ChNPs) is reported to have other biological properties such as anti-cancerous, antifungal, antioxidant activities, even induces an immune response in the plant, and helps manage biotic and abiotic stresses. Chitosan can also find its application in wastewater treatment, hydrating agents in cosmetics, the food industry, paper, and the textile industry as adhesive, drug-delivering agent in medical as well as for bioimaging. Since chitosan has low toxicity, the nano-formulation of chitosan can be used for the controlled release of fertilizers, pesticides, and plant growth promoters in agriculture fields. The ChNPs applications in precision farming being a novel approach in recent developments. Here we have comprehensively reviewed the major points in this review are; the synthesis of ChNPs by biological resources, their modification and formulation for increasing its applicability, their modified types, and the different agricultural applications of ChNPs. Abstract : Biological synthesis; Chitosan nanoparticles (ChNPs); Fertilizer; Fungicidal agent; Plant growth promoter.